LEACHING STUDY OF NICKEL PIG IRON (NPI) POWDER IN SULFURIC ACID MEDIUM AT ATMOSPHERIC PRESSURE USING HYDROGEN PEROXIDE AS OXIDIZING AGENT - Sucipto, Nurfauziah
Nickel pig iron (NPI) is ferronickel with a lower nickel content, and most of it is further processed into stainless steel. In an effort to meet the nickel demand for the battery industry, NPI can be utilized by extracting nickel and cobalt, as well as iron which can be processed into iron phosphate for the cathode of LiFePO4 type lithium-ion batteries. Meanwhile, nickel and cobalt can also be further processed into pure nickel sulfate and cobalt sulfate as raw materials for NMC type battery cathodes. In this research, metal extraction from NPI powder was studied by leaching method in acid solution using H2O2 as oxidizing agent